Blocking the apolipoprotein E/Amyloid β interaction in triple transgenic mice ameliorates Alzheimer's disease related amyloid β and tau pathology - Shan Liu; Ariel Breitbart; Yanjie Sun; Pankaj Mehta; Allal Boutajangout; Henrieta Scholtzova; Thomas Wısnıewskı (2013)
Inheritance of the apolipoprotein E4 (apoE4) genotype has been identified as the major genetic risk factor for late-onset Alzheimer's disease (AD). Studies have shown that the binding between apoE and amyloid-β (Aβ) peptides occurs at residues 244-272 of apoE and residues 12-28 of Aβ. ApoE4 has been implicated in promoting Aβ deposition and impairing clearance of Aβ. We hypothesized that blocking the apoE/Aβ interaction would serve as an effective new approach to AD therapy. We have previously shown that treatment with Aβ12-28P can reduce amyloid plaques in APP/PS1 transgenic (Tg) mice and vascular amyloid in TgSwDI mice with congophilic amyloid angiopathy. In the present study, we investigated whether the Aβ12-28P elicits a therapeutic effect on tau-related pathology in addition to amyloid pathology using old triple transgenic AD mice (3xTg, with PS1M146V , APPSwe and tauP30IL transgenes) with established pathology from the ages of 21 to 26 months. We show that treatment with Aβ12-28P substantially reduces tau pathology both immunohistochemically and biochemically, as well as reducing the amyloid burden and suppressing the activation of astrocytes and microglia. These affects correlate with a behavioral amelioration in the treated Tg mice.